ANALYSIS OF KAPAL ISAP PRODUKSI I STRUCTURES USING FINITE ELEMENT METHOD - YUAN MANDIKA (NIM : 131 05 028); pembimbing : Dr. Ir. Bagus Budiwantoro, PRIMADA
The function of suction dredger is to dredge, raise, and dislocate the materials from the deep to the surface. Kapal Isap Produksi I is the property of Indonesian tin mining company that operates especially in offshore use. The strength of the suction dredger can be derived by analyzing the strength of their main structures. In this thesis, analysis of the main structures is specialized in main top and ladder structures. If detected some failure of the structure, the modification of the structure is important. Processing with ANSYS Workbench 11.0 program gives the maximum stress of the ladder in upper condition with the value of 159,9 Mpa. In the down ladder position, the maximum stress condition identified as 42,5 MPa. Main top structure has the maximum stress of 114,3 MPa. The safety factor of both top and ladder structure has the value below the allowable safety factor. Therefore, modification is needed for the ladder and the main top of structure in particular, so the value of maximum stress will be decreased. Modification gives the higher value of safety factor. Structure of ladder and main top of KIP has a few of modification. The modification that gives the safety factor above the allowable value is the modification number two. In the analysis of ladder structure, the upper position of the ladder has the maximum stress greater than down ladder.